2015
DOI: 10.5558/tfc2015-069
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and the forest sector: Perception of principal impacts and of potential options for adaptation

Abstract: As evidence points to the importance of climate change (CC) impacts on forests, it is critical to understand how forestry and forest-dependent communities will be affected. People active in the Quebec forest sector were consulted about their perceptions on the most important potential impacts and adaptation measures. Preoccupations covered many aspects of natural ecosystems, forest-based communities, and industries. Expected impacts and adaptation measures were grouped according to biomes and sectors. Prioriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…Based on our results, the Canadian forest sector shows a greater consensus (almost 90%) on the cause of climate change than the general public in Canada (40.0%) [ 34 , 35 ]. This high acceptance of the reality and causes of climate change has already been pointed out by previous smaller-scale studies in some Canadian provinces [ 15 , 18 , 36 ], but our study highlights that it applies throughout the territory. The forest sector has similarly shown more awareness of climate change than the general population in several European countries [ 13 , 37 39 ], likely due to the direct impact of climate and its associated disturbances on the source of their economic well-being.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Based on our results, the Canadian forest sector shows a greater consensus (almost 90%) on the cause of climate change than the general public in Canada (40.0%) [ 34 , 35 ]. This high acceptance of the reality and causes of climate change has already been pointed out by previous smaller-scale studies in some Canadian provinces [ 15 , 18 , 36 ], but our study highlights that it applies throughout the territory. The forest sector has similarly shown more awareness of climate change than the general population in several European countries [ 13 , 37 39 ], likely due to the direct impact of climate and its associated disturbances on the source of their economic well-being.…”
Section: Discussionsupporting
confidence: 81%
“…These results are encouraging from a policy point of view since the inability to predict impacts with sufficient detail and certainty (i.e. uncertainty aversion) has been commonly identified as one of the main barriers to implementation of adaptive practices [ 15 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Climate change has received increased attention by researchers and policy makers (see, for example, Spittlehouse and Stewart 2004;Lindner et al 2010;Keenan 2015;Seidl et al 2016), but more knowledge does not necessarily translate into greater acceptance, nor into behavioural change (Kahan et al 2012). Research and knowledge development must be coupled with effective communication in order to be successful (Morin et al 2015). For example, regarding the performance of mixed versus pure stands, Carnol et al (2014) have shown a discrepancy between the perceptions of practitioners and the scientific knowledge on the issue of productivity in mixed species stands, urging to the need to address the lack of scientific data and to improve the communication of the topic towards practitioners through efficient information flow.…”
Section: Adaptation In Forest Managementmentioning
confidence: 99%